Determination of domestic wastewater chracteristics and its relation to the type and size of developments [electronic resource] - 252839 Sohaimi Kling; Mohd. Azraai Kassim (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Awam) - Universiti Teknologi Malaysia, 2007